The effects of chronic betaine supplementation on body composition and performance in collegiate females: a double-blind, randomized, placebo controlled trial - Jason Michael Cholewa; Andrea Hudson; Taylor Cicholski; Amanda Cervenka; Karley Barreno; Kayla Broom; McKenzie Barch; Stuart A. S. Craig (Taylor & Francis Group, 2018)
Background Betaine supplementation has been shown to improve body composition and some metrics of muscular performance in young men; but, whether betaine enhances body composition or performance in female subjects is currently unknown. Therefore, the purpose of this study was to investigate the interaction between resistance training adaptation and chronic betaine supplementation in females. Methods Twenty-three young women (21.0 ± 1.4 years, 165.9 ± 6.4 cm, 68.6 ± 11.8 kg) without prior structured resistance training experience volunteered for this study. Body composition (BodPod), rectus femoris muscle thickness (B-mode Ultrasound), vertical jump, back squat 1RM and bench press 1RM were assessed pre- and post-training. Following 1 week of familiarization training, subjects were matched for body composition and squat strength, and randomly assigned to either a betaine (2.5 g/day; n = 11) or placebo (n = 12) group that completed 3 sets of 6-7 exercises per day performed to momentary muscular failure. Training was divided into two lower and one upper body training sessions per week performed on non-consecutive days for 8 weeks, and weekly volume load was used to analyze work capacity. Results Significant main effects of time were found for changes in lean mass (2.4 ± 1.8 kg), muscle thickness (0.13 ± 0.08 cm), vertical jump (1.8 ± 1.6 cm), squat 1RM (39.8 ± 14.0 kg), and bench press 1 RM (9.1 ± 7.3 kg); however, there were no significant interactions. A trend (p = .056) was found for greater weekly training volumes for betaine versus placebo. Significant interactions were found for changes in body fat percentage and fat mass: body fat percentage and fat mass decreased significantly more in betaine (− 3.3 ± 1.7%; − 2.0 ± 1.1 kg) compared to placebo (− 1.7 ± 1.6%; − 0.8 ± 1.3 kg), respectively. Conclusions The results of this study indicated that betaine supplementation may enhance reductions in fat mass, but not absolute strength, that accompany a resistance training program in untrained collegiate females.